Anatomical, histological and immunohistochemical study of the tongue in the rainbow trout (Oncorhynchus mykiss). (24th July 2020) - Abbate, Francesco; Guerrera, Maria Cristina; Levanti, Maria; Laurà, Rosaria; Aragona, Marialuisa; Mhalhel, Kamel; Montalbano, Giuseppe; Germanà, Antonino
Abstract: The rainbow trout ( Oncorhynchus mykiss Walbaum, 1792) is a fish commercially farmed all over the world. These fish are usually fed, in aquaculture, with pellets rich in proteins and fat. It is well known that there are close relationships among the adaptation of vertebrates to their environment, the capacity and the modality of feeding and the oral cavity morphology, especially the tongue one. No data are so far available about the morphology of the rainbow trout tongue, and therefore, the aim of this study was to investigate by light, scanning electron and confocal laser microscopy, the morphological characteristics of the tongue. An apex, a body and a root can be distinguished in the tongue, and the presence of teeth, taste buds and fungiform‐like papillae was demonstrated. Light microscopy shows the presence of an adipose tissue pad in the deeper layer of the apex and in the most superficial layer of the root. In the deeper layer of the body, a triangular‐shaped pad consisting of fusiform cells immersed in abundant extracellular matrix of the mesenchymal tissue was observed. The confocal laser microscopy shows the presence of cells with a fibroblast‐like morphology positive for vimentin. In the deepest layer of the tongue root, a large area of osteo‐cartilaginous tissue was observed. The results, besides the description of the morphological characteristics of the tongue, related to studies regarding the feeding, could be considered for the eventual applications of the use of mesenchymal cells, observed in adult fish, in cell therapies in different pathologies.